Historia de Rosa . Rosa's Story - Jaugey, Florence (Camila Films, 2005)
Verzio FF submission In 2003, Nicaraguan 9-year-old Rosa was snatched and raped by a stranger. Five weeks later they found out the girl was pregnant. Her parents wanted her to get an abortion. The case mobilized international organizations that gave support to the parents’ wish, but it also came to the attention of the government and the church, which were against the abortion. The case shocked Nicaragua and aroused an international debate about abortion.